EFFECT OF SERVICE QUALITY ON SERVICE USER SATISFACTION AT CEMPAKA LIMA BANDA ACEH CLINIC - Rizka Rizka; Iqlima Azhar (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
The purpose of this study was to find out the Effect of Service Quality on Service User Satisfaction at Cempaka Lima Clinic in Banda Aceh, where the number of samples in the study was 30 respondents using incidental sampling method with a 10% error rate. The method in this study is descriptive quantitative. data collection techniques, namely questionnaires and observations. data analysis techniques using slovin formulas. The study used four free variables and one bound variable. Based on the results of the study it is known that The Quality of Service contributes to the improvement of Customer Satisfaction the results of the research obtained t count value > t table or 2,931 > 1,699, so it can be concluded that the third hypothesis (responsiveness) is accepted. calculation of Test F where obtained the calculated value of F of 7,346 with a significance value of 0.000, because the calculated F value (7,346) is greater than the table F (4.18) it can be concluded that independent variables including Physical Evidence, Reliability, Responsiveness, Guarantee have a simultaneous influence of R2 of 0.540 which means 54.0% customer satisfaction can be explained by service quality variables (independent variables), the remaining 46.0% explained by other factors outside the model